The VATO project: An original methodology to study the transfer of tritium as HT and HTO in grassland ecosystem. (February 2017) - Maro, D.; Vermorel, F.; Rozet, M.; Aulagnier, C.; Hébert, D.; Le Dizès, S.; Voiseux, C.; Solier, L.; Cossonnet, C.; Godinot, C.; Fiévet, B.; Laguionie, P.; et al.
Abstract: Tritium ( 3 H) is mainly released into the environment by nuclear power plants, military nuclear facilities and nuclear reprocessing plants. The construction of new nuclear facilities in the world as well as the evolution of nuclear fuel management might lead to an increase of 3 H discharges from the nuclear industry. The VATO project was set up by IRSN (Institut de Radioprotection et de Sûreté Nucléaire) and EDF (Electricité de France) to reduce the uncertainties in the knowledge about transfers of 3 H from an atmospheric source (currently releasing HT and HTO) to a grassland ecosystem. A fully instrumented technical platform with specifically designed materials was set up downwind of the AREVA NC La Hague reprocessing plant (Northwest of the France). This study, started in 2013, was conducted in four main steps to provide an hourly data set of 3 H concentrations in the environment, adequate to develop and/or validate transfer models. It consisted first in characterizing the physico-chemical forms of 3 H present in the air around the plant. Then, 3 H transfer kinetics to grass were quantified regarding contributions from various compartments of the environment. For this purpose, an original experimental procedure was provided to take account for biases due to rehydration of freeze-dried samples for the determination of OBT activity concentrations in biological samples. In a third step, the 3 H concentrations measured in the air and in rainwater were reconstructed at hourly intervals. Finally, a data processing technique was used to determine the biological half-lives of OBT in grass. Highlights: Physico-chemical forms of tritium in air. Tritium transfer kinetics in grass. Original procedure to avoid biases due to sample rehydration. Biological half-lives of OBT in grass.